Highly anisotropic functional conductors fabricated by multi-melt multi-injection molding (M3IM): A synergetic role of multiple melt flows and confined interface. (8th February 2019) - Huang, Yanhao; Liu, Zhengying; Chen, Rui; Zheng, Shaodi; Feng, Changping; Chen, Libo; Yang, Wei; Yang, Mingbo
Abstract: An anisotropic conductor with graphene nanoplatelets (GNPs) well planar aligned in PP matrix has been obtained in this work through multi-melt multi-injection molding (M 3 IM). In this method, a second composite melt penetrated the first melt and products with three layers (skin layer, intermediate layer and core layer) were obtained. The GNPs in the three layers was entirely planar oriented along machine direction (MD) owing to the second shear flow and confined interface between intermediate layer and core layer. The finely aligned structure drastically elevated in-plane thermal conductivity of intermediate layer to as high as 7.32 W m −1  K −1 and highlighted an average thermal conductive anisotropy of 20.86 under 25 wt % GNPs loading, as well as provided a good electric conductivity of 0.03 S m −1 in MD while insulativity in perpendicular direction. Additionally, the M 3 IM composite performed well in mechanical properties with tensile strength (40.33 MPa) and Young's modulus (1.15 GPa). This M 3 IM manufacturing provides outstanding anisotropic properties to the injection products which possess a considerable potential application in unilateral conduction field. Graphical abstract: